The Revolution which toppled the Umayyads : Neither Arab nor Ἁbbāsid - Agha, Saleh Said, (Islamic History and Civilization ;, 2003)
This book re-examines the so-called Ἁbbāsid revolution, the ethnic character of whose effective constituency has been contested for over eight decades. It also brings to question the authenticity of the Ἁbbāsid dynastic claim. To establish its two theses (neither Arab nor Ἁbbāsid) this book employs, in its three parts, three distinct methodological approaches. To reconstruct the secret history of the clandestine Organization, Part One elicits a narrative through a rigorous application of the historical-critical method. Part Two subjects to close textual analysis some prime-grade literary specimen. In Part Three, a purely quantitative approach is adopted to study the demographic character of the formal structures of leadership within the Organization. History, historiography, heresiography, literature, the narrative, the textual analysis, and the quantitative approach, cannot be less inseparable.